Types of Narration in Literary Works - Ganieva Orzigul Khayriddinovna (Euro Asian Journal Publishing, 2024)
A literary text serves numerous tasks, including embodying the work's essence, demonstrating the possibilities of language and imagery, merging the author's various stylistic approaches, and providing aesthetic pleasure to readers. In literary works authors strive to express their vision through their own speech or characters’ speeches, which can be termed as author-narrator's speech and character-narrator’s speech. The following paper discusses the privileges of both these speeches through analysis of extracts from the novels “Justice Venue” by Adil Yakubov and “As I Lay Dying” by William Faulkner. A skilled writer achieves objectivity through the speech of a hero, and increases the power of artistic and aesthetic influence on the reader
Keywords: narration; author; character